Secondhand smoke exposure and dyslipidemia among non‐smoking adults in the United States. (30th July 2021) - Okekunle, Akinkunmi Paul; Asowata, Jeffery Osahon; Adedokun, Babatunde; Akpa, Onoja Matthew
Abstract: Dyslipidemia is a major public health challenge worldwide and whether secondhand smoke exposure (SHSE) is associated with dyslipidemia is yet to be understood. This study evaluated the relationship between SHSE and odds of dyslipidemia among adults in the United States. We identified 3064 adults who had never smoked in the 2015–2016 National Health and Nutrition Examination Survey and estimated the odds ratio and 95% confidence interval for the relationship between SHSE and odds of dyslipidemia using a multivariable adjusted‐logistic regression at a two‐sided p < 0.05. Overall, the mean age of respondents was 46.4 ± 18.0 years, 59.6% had dyslipidemia and 36.2% had SHSE. The odds of dyslipidemia among individuals with SHSE were 1.148 (1.147, 1.149) in the overall sample, 1.214 (1.214, 1.215) among women and 1.165 (1.163, 1.167) among men. The odds trended similarly independent of age groups: 1.130 (1.129, 1.131) for young adults (<60 years) and 1.304 (1.300, 1.308) for old adults (≥60 years). SHSE was associated with higher odds of dyslipidemia with higher odds among women and old adults. Primary intervention(s) targeted at reducing SHSE may show benefits in reducing the odds of dyslipidemia, and longitudinal studies would be necessary to clarify the association between SHSE and dyslipidemia.